2021
DOI: 10.1002/smll.202104302
|View full text |Cite
|
Sign up to set email alerts
|

Acidic TME‐Responsive Nano‐Bi2Se3@MnCaP as a NIR‐II‐Triggered Free Radical Generator for Hypoxia‐Irrelevant Phototherapy with High Specificity and Immunogenicity

Abstract: Here, acidic tumor microenvironment (TME)‐responsive nano‐Bi2Se3@MnCaP, as a near‐infrared‐II (NIR‐II) biowindow‐triggered free radical generator for hypoxia‑irrelevant phototherapy, is elaborately developed by biomimetic mineralization of MnCaP onto 2, 2′‐azobis[2‐(2‐imidazolin‐2‐yl)propane] dihydrochloride (AIPH)‐loaded mesoporous nano‐Bi2Se3 to form Bi2Se3/AIPH@MnCaP (BAM). Surface mineral of MnCaP can be degraded under mild acidity, leading to the release of both Mn2+ and AIPH. The leached Mn2+ not only fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Due to the advantages of high spatiotemporal resolution, low side effects, and noninvasiveness, photothermal therapy (PTT) has been recognized as an ideal modality in combination with TDT. 22 Up to now, nanomaterial-based photothermal agents, such as gold nanocages (AuNCs), 23 Nb 2 C Mxene nanosheets, 24 CuFeSe 2 nanoparticles, 25 and Bi 2 Se 3 nanocomposites, 26 have successfully achieved hyperthermiaaugmented free radical-based therapy under near-infrared (NIR) laser irradiation. However, the leaked AIPH during circulation may slowly decompose at physiological temperature, causing undesired off-target toxicity to normal cells.…”
Section: •−mentioning
confidence: 99%
“…Iron-based nanomaterials can dissolve ferrous ions under the mildly acidic conditions of the tumor microenvironment and initiate the Fenton reaction to overproduce H 2 O 2 , which results in the generation of reactive oxygen species (ROS), ·OH to trigger apoptosis and to inhibit tumors; this newly defined therapeutic strategy is chemodynamic therapy (CDT) [ 28 30 ]. Metal–organic framework NPs will degrade in the acidic microenvironment of solid tumors and release loaded drug [ 31 , 32 ]. Through a judicious choice of inorganic and organic components, the chemical functionalities and crystalline structure of metal–organic frameworks can be deliberately modulated to be utilized for CDT and to function as a siRNA delivery system [ 33 ].…”
Section: Introductionmentioning
confidence: 99%